MULTICULTURAL EDUCATION IN FORMING ATTITUDE TOLERANCE OF DIVERSITY IN PRIMARY SCHOOL STUDENTS - Nathania, Nasywa; Sarifah, Iva; Yudha, Chrisnaji Banindra (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2024)
Education is a progressive approach that continues to move towards change in the world of education. It is an inseparable aspect of the education system, which makes multicultural education inseparable from tolerance because both are part of the national education system. Tolerance is a person’s ability to respect and treat other people with a complete understanding of all existing differences. This research aims to describe how multicultural education plays a role in instilling an attitude of tolerance in elementary school students based on theory. This article also discusses the components and objectives of multicultural education and strategies for implementing multicultural education in elementary schools. Researchers used the literature study method or library research, which collected relevant data about multicultural education and its relationship with tolerance. This data was then studied to find new scientific facts.